Nicotine-mediated therapy for Parkinson’s disease in transgenic Caenorhabditis elegans model - Ullah, Inam; Zhao, Longhe; Uddin, Shahab; Zhou, Yangtao; Wang, Xin; Li, Hongyu (Frontiers in Aging Neuroscience, 2024)
Parkinson’s disease resultant in the degeneration of Dopaminergic neurons and accumulation of α-synuclein in the substantia nigra pars compacta. The synthetic therapeutics for Parkinson’s disease have moderate symptomatic benefits but cannot prevent or delay disease progression. In this study, nicotine was employed by using transgenic Caenorhabditis elegans Parkinson’s disease models to minimize the Parkinson’s disease symptoms. The results showed that the nicotine at 100, 150, and 200 μM doses reduced degeneration of Dopaminergic neurons caused by 6-hydroxydopamine (14, 33, and 40%), lowered the aggregative toxicity of α-synuclein by 53, 56, and 78%, respectively. The reduction in food-sensing behavioral disabilities of BZ555 was observed to be 18, 49, and 86%, respectively, with nicotine concentrations of 100 μM, 150 μM, and 200 μM. Additionally, nicotine was found to enhance Daf-16 nuclear translocation by 14, 31, and 49%, and dose-dependently increased SOD-3 expression by 10, 19, and 23%. In summary, the nicotine might a promising therapy option for Parkinson’s disease.